Obtaining employee commitment to living the brand of the organisation - G. Boyd; M. Sutherland (South African Journal of Business Management, 2006)
In the competitive business environment, brand management is viewed as a critical success factor. The importance of building a brand-centric organisation in which employees are ambassadors for the brand is often espoused, but there has been little empirical evidence of how managers should set about achieving this. This exploratory qualitative study consisted of four case studies in organisations where employees are acknowledged to `live the brand' to obtain empirical evidence of those factors that influenced employee performance. The study uncovered six key practices that managers should implement in an integrated manner when driving an intervention to enable employees to live the brand. The findings also contradict some of the human resource literature in what was found to be unimportant.
Keywords: 650